Environmentally Smart Design: Designing for Social Wellbeing Across the City and in the Workplace. (March 2017) - McGregor, Alisdair; Aguilar, Ann Marie; Lockhart, Victoria
Abstract : Sustainable need not mean more expensive. Health problems caused by sedentary lifestyles, pollution and injuries from road accidents come at great financial cost — not just for individuals, but also for employers and indeed national governments. Built environments designed to keep people active and away from harm are thus economically beneficial, too.Alisdair McGregor, Ann Marie Aguilar and Victoria Lockhart of Arup cite some of the company's recent schemes in New York and London that have successfully encouraged cycling, strolling and other healthy behaviours, while also avoiding contributing to climate change.